Effect of Mirtazapine on Gastric Oxidative Stress and DNA Injury Created With Methotrexate in Rats - Demiryilmaz, Ismail; Uzkeser, Hulya; Cetin, Nihal; Hacimuftuoglu, Ahmet; Bakan, Ebubekir; Altuner, Durdu (Asian Journal of Chemistry, 2012)
In this study, effect of mirtazapine on gastric oxidative stress and DNA injury created with methotrexate was investigated. Experimental results showed that GSH (nmol/g protein), MDA (μmol/g protein) and MPO (μ/g protein) in the gastric tissue of the control group rats receiving methotrexate are 4.97 ± 0.37, 2.78 ± 0.30 and 3.12 ± 0.18, respectively. GSH, MDA and MPO measurements in the gastric tissue of rats receiving mirtazapine + methotrexate were detected to be 9.23 ± 0.51(p < 0.0001), 1.80 ± 0.31(p < 0.0001) and 1.63 ± 0.25 (p < 0.0001), respectively. GSH, MDA and MPO values in the intact rat group were found 8 ± 0.38 (p < 0,0001), 1.63 ± 0.28 (p < 0.0001) and 1.37 ± 0.21 (p < 0.0001), respectively. In addition, while 8-ohdG/dG quantity that DNA injury product in the control group administered methotrexate was 2.4 ± 0.11 pmol/L, this quantity was 1.3 ± 0.14 pmol/L (p < 0.001), 1.1 ± 0.10 pmol/L (p < 0.001) in mirtazapine and intact group, respectively. As a result, it was seen that mirtazapine prevents increase of oxidative stress and DNA injury created with methotreaxete in the gastric tissue of rat.